EC trade policy beyond 1992 - Georg Koopmann; Hans-Eckart Scharrer (Intereconomics, 1989)
The initiative to set up the single European market has aroused fears abroad, and indeed even within Europe itself, that the intention is to turn the Community into a “Fortress Europe”. Attempts to allay these fears by the Council of Ministers, the EC Commission or individuals representing them have achieved little success, and on occasion have actually tended to be counter-productive. Is “Fortress Europe” an illusion or a real danger?
Keywords: 330; European Community